Hydrothermale synthese von konjugierten polymeren am beispiel von pyrronpolymeren und polybenzimidazolen - Taublaender,MJ; Mezzavilla,S; Thiele,S; Glöcklhofer,F; Unterlass,MM (Angewandte Chemie, 2020)
Various polyimides and polyamides have recently been prepared by hydrothermal synthesis in nothing but H 2 O under high pressure and high temperature conditions. However, none of these polymers have a conjugated polymer backbone. We hereby report an extension of the synthetic scope of this simple and naturally environmentally friendly polymerisation technique to the production of conjugated polymers. Selected representatives of two different polymer classes, pyrron polymers and polybenzimidazoles, were synthesized hydrothermally. In addition to a mechanistic discussion of polymer formation, an electrochemical characterization of the most promising product is presented.